The impact of financial policy on the sustainable development of business entities in post-pandemic Georgia - Katamadze, Giorgi (European Journal of Sustainable Development, 2024)
Financial institutions form a strong link in the chain of business operations of the modern world; in addition, they may also be thought of as a binder. During the Covid -19 pandemic the financial institutions all over the world, and in Georgia as well, faced a number of problems and challenges: on one hand, there was a large number of consumers and mortgage loans to individuals, and on the other hand, loans issued to business entities for working capital and fixed assets, real estate purchase and other purposes turned out to form the major part of their loan portfolio. The pandemic has led the natural persons, as well as legal entities into a force majeure situation, while the decisions of financial institutions were crucial for their viability. However, the purpose of the study is to consider the impact of lending policies on business entities and their development processes. The paper discusses the policies of financial institutions during the Covid-19 pandemic and the post-pandemic period, the chronology of the decisions made and the outcomes of such decisions based on available official data, also the impact of lending on business entities and identifies modern trends and challenges. The research methodology was determined based on the research objectives and included the following methods: the paper analyzes the decisions made by the National Bank of Georgia before and after the pandemic, in relation with the official data on loans and financial transactions that the National Bank generated. Within the framework of the research, in order to determine the level of influence of the financial institutions on current economic processes in Georgia, the paper analyzes the results of their activities, which are based on official data from the National Bank of Georgia and empirical material collected. Keywords: Financial institutions; Lending policy; National Bank of Georgia; Post-pandemic economic policy; JEL Classification: G2; G21; E5; E58; E6; Acknowledgement: